A new constant market share competitiveness index - Abdul Jalil, Mohd Aisha Nuddin; Abdul Karim, Mohd Azhar; Gan, V. B. Y.; Khalifah, N. A. (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
Constant-market-share analysis (CMSA) is one of the most widely employed descriptive tool for measuring the export competitiveness of a country relative to other countries or regions of trade for goods and services. Typically, export growth is attributed to growth in the country’s export competitiveness and also to the growth effect of the market itself. However, CMSA measurement is prone to a number of methodological short comings which stems from the CMS identities used in the analysis. Namely, the discrete approximation of continuously changing trade patterns, the interaction effects term residual from the CMS identity decomposition and the arbitrary choice of weights attached to base periods. This paper addresses some of the short comings of the classic CMSA approach. Within a geometric framework we reexamine the CMS decomposition and propose a new net-share approach that is easier to implement and interpret. For researchers and policy makers, this methodology presents a simpler but more consistent measurement for more accurate CMS measurement and interpretations of changing trade patterns.